Sildenafil has little influence on cardiovascular hemodynamics or 6-km time trial performance in trained men and women at simulated high altitude - Jacobs, K. A.; Kressler, J.; Stoutenberg, M.; Roos, B. A.; Friedlander, A. L. (High Altitude Medicine & Biology, 2011)
Sildenafil improves maximal exercise capacity at high altitudes (4350-5800?m) by reducing pulmonary arterial pressure and enhancing oxygen delivery, but the effects on exercise performance at less severe altitudes are less clear. Purpose: To determine the effects of sildenafil on cardiovascular hemodynamics (heart rate, stroke volume, and cardiac output), arterial oxygen saturation (SaO2), and 6-km time-trial performance of endurance-trained men and women at a simulated altitude of 3900 m. Methods: Twenty men and 15 women, endurance-trained, completed one experimental exercise trial (30 min at 55% of altitude-specific capacity +6-km time trial) at sea level (SL) and two trials at simulated high altitude (HA) while breathing hypoxic gas (12.8% FIo2) after ingestion of either placebo or 50 mg sildenafil in double-blind, randomized, and counterbalanced fashion. Results: Maximal exercise capacity and SaO2 were significantly reduced at HA compared to SL (18%-23%), but sildenafil did not significantly improve cardiovascular hemodynamics or time-trial performance in either men or women compared to placebo and only improved SaO2 in women (4%). One male subject (5% of male subjects, 2.8% of all subjects) exhibited a meaningful 36-s improvement in time-trial performance with sildenafil compared to placebo. Conclusions: In this group of endurance trained men and women, sildenafil had very little influence on cardiovascular hemodynamics, SaO2, and 6-km time-trial performance at a simulated altitude of 3900 m. It appears that a very small percentage of endurance-trained men and women derive meaningful improvements in aerobic performance from sildenafil at a simulated altitude of 3900 m.